Ustalenie tożsamości osoby – analiza działalności wybranej jednostki Policji, studium przypadków – część 2 - Wojnicz, Piotr; Sękowska, Izabela (Civitas et Lex, 2020)
Establishing the identity of the dead and the living person is an important element in the functioning of every society. Giving them names is respect for their dignity and a humane approach to every human being. As important as this sphere of life is the state institutions have worked out quite meticulous procedures to regulate the issue.